Karakter Qur’ani Mahasiswa di Era Digital: Studi Tematik tentang Tabayyun, Etika Bertutur, dan Tanggung Jawab Digital - Muhammad Nur Fauzan; Mardian Idris Harahap (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2025)
The acceleration of the digital ecosystem drives an information flow that is difficult to filter and gives rise to ethical challenges for the religious academic community. Grounded in the values of the Qur’an, this study focuses on the Qur’anic character of students in three practical domains: information verification (tabayyun), ethics of speech (qaulan), and digital responsibility (amanah). The aim of the study is to examine two core questions: (1) how students apply verification before sharing information; and (2) how Qur’anic speech ethics are implemented in digital interactions—and how the dimensions of digital responsibility (permission, attribution, privacy, security) accompany them. The method used is thematic exegesis (mawḍū‘ī) to map the normative foundations of the Qur’an related to these three values, combined with a descriptive qualitative approach through in-depth interviews and light observation in the context of students’ academic/online communication. The data were analyzed thematically with validity assurance through triangulation and member checking. The findings show the emergence of growing epistemic caution—evident from efforts to delay uploading when in doubt, tracing sources, and comparing references—although consistency is not yet uniform across all channels. In the dimension of speech, the tendency to use clarificatory diction, avoid personal attacks, and include references has increased, while in the domain of amanah, the practices of asking permission and giving attribution are relatively understood, but technical aspects (account security, metadata management, privacy protection) remain weak. The practical implication is the need for operational indicators and concise Qur’an-based digital literacy SOPs at the study program level, including multisource verification protocols, data-anchored clarification formats, and responsibility checklists. Conceptually, this study enriches the literature on Qur’anic character in the platform era while also providing an evaluative baseline for strengthening a culture of academic communication that is valid, courteous, and responsible.